A histological study of the alimentary canal and associated structures in the larva of Coryphodema tristis Drury (Lepidoptera) - Meyer, A. J.(Albertus Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. Agric.) -- University of Stellenbosch, 1965.